KOMPARASI KINERJA KEUANGAN BANK SYARIAH DI INDONESIA DAN BANK SYARIAH DI MALAYSIA PADA MASA PANDEMI COVID 19 DENGAN PENDEKATAN SHARIA CONFORMITY AND PROFITABILITY (SCnP) - Mahmud Syukri; Suryani Suryani; Efi Syarifudin (Al Amin: Jurnal Kajian Ilmu dan Budaya Islam, 2023)
The Covid-19 pandemic has affected almost all aspects of life, especially in the financial industry sector, namely banking. The direct impact includes three dimensions of risk, namely increasing non-performing financing on credit risk, decreasing value of Islamic Bank securities on market risk, and bank capital on liquidity risk. The purpose of this study was to compare the financial performance of Islamic banks in Indonesia and Malaysia during the Covid-19 pandemic using the Sharia Conformity and Profitability (SCnP) approach. This research is quantitative research that is used to answer problems with certain variables and is classified as comparative research with secondary data sources. The results of this study show that based on the Conformity and Profitability (SCnP) approach, Bank BTPN Syariah has been resilient during the Covid 19 pandemic with a good profit level. While the two Malaysian Sharia Banks showed a decline in financial performance, Bank Islam Malaysia Berhad was quite successful in maintaining financial performance. The Covid 19 pandemic has had quite an impact on Islamic banks in Indonesia, which have financing portfolios with sizable mudharabah musyarakah contracts which are quite large compared to Islamic Banks having financing portfolios with smaller mudharabah musyarakah contracts